Corrosion Behaviour of Metals in Artificial Tear Solution - Kumar, C.; Raj, A. John Amal; Selvaraj, S.K. (JOURNAL OF ADVANCES IN CHEMISTRY, 2016)
Human tear comes in contact with a number of instruments during operation in the eyes. This results in a variety of undesirable effects such as corrosion and malfunction. Corrosion behaviour of five metals, namely, mild steel (MS), mild steel coated with zinc (MS-Zn), Ni-Cr, Ni-Ti super elastic (Ni-Ti.SE), and SS 316 L in artificial tear solution has been studied by polarization study and AC impedance spectra. The study reveals that the decreasing order of corrosion resistance in artificial tear solution is : Ni-Ti SE > Ni-Cr > SS 316 L > MS-Zn > MS. The first three metals are better candidates and the first one is the best candidate for making instruments used in operation in the eyes, in presence of tears.